2017
DOI: 10.1021/acscatal.7b01036
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and DFT Studies of Photoredox Carbon–Carbon Bond Cleavage Reactions by Molecular Vanadium Catalysts under Ambient Conditions

Abstract: Visible light assisted photocatalytic organic reactions have recently received intense attention as a versatile approach to achieve selective chemical transformations, including C-C and several C-X (X = N, O, S) bond formations under mild reaction conditions. The light harvesters in previous reports predominantly comprise ruthenium or iridium photosensitizers. In contrast, selective, photocatalytic aliphatic C-C bond cleavage reactions are scarce. The present study focuses on rationally designing V V oxo compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 27 publications
(72 reference statements)
5
69
0
Order By: Relevance
“…[48] As such, the HOMO energy level of the complex could be stabilized, and the oxida-tion potential of the V V photocatalyst was increased. [48] As such, the HOMO energy level of the complex could be stabilized, and the oxida-tion potential of the V V photocatalyst was increased.…”
Section: V Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] As such, the HOMO energy level of the complex could be stabilized, and the oxida-tion potential of the V V photocatalyst was increased. [48] As such, the HOMO energy level of the complex could be stabilized, and the oxida-tion potential of the V V photocatalyst was increased.…”
Section: V Complexesmentioning
confidence: 99%
“…It was found that the redox of noninnocentl igands (i.e.,h ydrazonei midate) was essential for photocatalytic activity.I na follow-up study,alibrary of modified V V photocatalysts were developed, and stronge lectron-withdrawing groups such as NO 2 and Fw ere introduced at specific locations of the ligand at which the spin density was located. [48] As such, the HOMO energy level of the complex could be stabilized, and the oxida-tion potential of the V V photocatalyst was increased. In particular,t he complex having pentafluoro substituents on the imidate and one nitro group on the aryl hydrazone gave the greatest activity according to kinetics measurements, with areaction rate that was up to seven times faster than that of the originalc omplex.…”
Section: V Complexesmentioning
confidence: 99%
“…[57,58] While compounds with aromatic substituents show lifetimes below 200 ns with quantum yields < 1%,c omplexes with bulky alkyl substituents (R = adamantyl, tert-butyl) exhibit longer-lived emission with lifetimes and quantum yields of up to 15.1 msa nd 20 %, respectively.M ore recently,h ydrazone-imidate vanadium(V) oxo complexes with luminescence lifetimes of up to 9.9 ns in acetonitrile have been utilized in photocatalysis. [59,60] The exciteds tate was assigned as LMCT (O 2À !V V )v ia density functional theory.…”
Section: Introductionmentioning
confidence: 99%
“…However, Reisner's photocatalysts contained the highly toxic Cd, whereas Stephenson's system involved expensive Ir complexes. Our team has been at the forefront of using earth‐abundant, less toxic vanadium photocatalysts to effect C−C bond cleavage in lignin model compounds (Figure a) that can be characterized more thoroughly . We observed a remarkably selevtive C‐C bond cleavage at the aliphatic aochols (red, bold bond in Figure b) mediated by a vanadium photocatalyst under ambient air .…”
Section: Pecs For Biomass Valorizationmentioning
confidence: 93%